MENINGKATKAN AKTIFITAS DAN HASIL BELAJAR SISWA MELALUI PENERAPAN MODEL STUDENT FACILITATOR AND EXPLAINING - Muhail, Muhail (Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 2021)
Abstract This research is a Classroom Action Research. Implemented collaboratively, between researchers, observers, and research subjects. The main objective of this research is to increase the activities and social studies learning outcomes in VII class through the application of the Student Facilitator and Explaining Model. The subjects of this research were class VII G SMP Negeri 1 Kramatmulya Kuningan for the 2019/2020 academic year which consisted of 30 students with a composition of 15 female students and 15 male students. The implementation of this research was carried out in the first (odd) semester of the 2019/2020 school year. This classroom action research process was carried out for two cycles, and two main actions, namely planning, implementing the action, observing, and reflecting. Before taking action, the researcher carries out a learning activity called the pre-cycle, then after that, he takes action in the form of the first and second cycles. At the end of each cycle, students’ activities were observed in following the learning process and a test was carried out using a question instrument. Then the results obtained at the first meeting and the second meeting are averaged to become the final result of each cycle. The results of the pre-cycle observation showed that only 13% of students were active. The average test result in the pre-cycle was 64.30 and only 17% reached the completeness where the KKM determined was 75.00. The results of the first cycle showed that active students increased to 40%, the average value of learning outcomes in the first cycle also increased to 70.50, and student completeness reached 50%. The results of the second cycle showed that active students increased to 83.30% as well as an increase in the average score to 77.50 where the percentage of completeness in learning also increased to 86.70%. Given that the results of the second cycle have passed the predetermined success indicators, the next cycle of action is not required. Keywords: Activity, Achievement, Learning, Student Facilitator and Explaining